Prevalence of hepatitis C virus genotypes in risk groups in the Republic of Macedonia: A 5 years survey. Issue 12 (19th August 2013) - Kiprijanovska, Sanja; Davalieva, Katarina; Noveski, Predrag; Sukarova‐Stefanovska, Emilija; Plaseska‐Karanfilska, Dijana
Abstract The prevalence of hepatitis C virus (HCV) genotypes depends on geographical location. HCV genotyping is important for epidemiological investigations and treatment management. The aim of this study was to determine the HCV genotype prevalence in the most prominent risk groups in the Republic of Macedonia in the last 5 years and to evaluate its association with patient's age, gender, and mode of transmission. A total of 1, 167 HCV positive patients, divided into three risk groups (intravenous drug use, chronic hemodialysis, and other risk factor), were genotyped using an in‐house ASO hybridization method with genotype‐specific oligonucleotide probes. The genotypes 1, 2, and 3 were present with 52.2%, 0.6%, and 47.0%, respectively. Genotype 1 was most prevalent in hemodialysis (89.0%) and other risk factor group (53.8%). It was found associated independently with hemodialysis, age >40 and female gender. Genotype 3 predominated in intravenous drug users (64.0%) and was associated significantly also with age ≤40 and male gender. Multivariable logistic regression analysis pointed out hemodialysis (P < 0.0001, Exp (B) = 12.0) as a positive predictor factor for genotype 1 and age ≤40 (P = 0.021, Exp (B) = 1.8) and intravenous drug use (P < 0.0001, Exp (B) = 8.4) as a positive predictor factors for genotype 3. In conclusion, the main transmission route of HCV infection in the Republic of Macedonia is intravenous drug use, followed by hemodialysis. HCV genotypes 1 and 3 dominate in these two most prominent risk groups in the Republic of Macedonia. J. Med. Virol. 85:2072–2078, 2013. © 2013 Wiley Periodicals, Inc.